Acute kidney injury and acute kidney disease in high-dose cisplatin-treated head and neck cancer - Trevisani, Francesco; Di Marco, Federico; Quattrini, Giulia; Lepori, Nicola; Floris, Matteo; Valsecchi, Davide; Giordano, Leone; Dell’Oca, Italo; Cardellini, Sara; Cinque, Alessandra; Mirabile, Aurora (Frontiers in Oncology, 2023)
Background In locally advanced head and neck squamous cell carcinoma (LA-SCCHN) at least 200mg/m2 (standard dose 300 mg/m2) of cisplatin concomitant with radiotherapy represents the standard of care, both in postoperative and conservative settings. Nevertheless, high dose administration every 3 weeks is often replaced with low dose weekly cisplatin to avoid toxicities like kidney injury, though often failing to reach the therapeutic dose. Our aim was to investigate the incidence of renal impairment in the real-life setting, integrating high dose cisplatin with adequate supportive therapy, and to explore both Acute Kidney Injury (AKI) and Acute Kidney Disease (AKD), a recently described clinical renal syndrome that encompasses functional alterations of the kidney lasting fewer than 3 months. Methods One hundred and nine consecutive patients affected by LA-SCCHN and treated with at least a cumulative dosage of 200 mg/m2 of cisplatin concomitant with radiotherapy were enrolled in this prospective observational study. Results AKI was reported in 12.8% of patients, 50% of whom were stage 1 (KDIGO criteria), while 25.7% of the cohort developed AKD. Patients with baseline estimated Glomerular Filtration Rate (eGFR) < 90 ml/min showed a higher incidence of AKD (36.2% vs 17.7%). Hypertension, baseline eGFR, and therapy with Renin-angiotensin-aldosterone system inhibitors proved to be significant factors associated with both AKI and AKD. Conclusion AKI and AKD are not rare complications of high-dose cisplatin, but an appropriate prevention strategy and accurate monitoring of patients during treatment could lead to a reduction of the burden of these conditions.